Xanthine Oxidase Mediates Axonal and Myelin Loss in a Murine Model of Multiple Sclerosis - Honorat, Josephe Archie (Public Library of Science, 2013)
OBJECTIVES: Oxidative stress plays an important role in the pathogenesis of multiple sclerosis (MS). Though reactive oxygen species (ROS) are produced by various mechanisms, xanthine oxidase (XO) is a major enzyme generating ROS in the context of inflammation. The objectives of this study were to investigate the involvement of XO in the pathogenesis of MS and to develop a potent new therapy for MS based on the inhibition of ROS. METHODS: XO were assessed in a model of MS: experimental autoimmune encephalomyelitis (EAE). The contribution of XO-generated ROS to the pathogenesis of EAE was assessed by treating EAE mice with a novel XO inhibitor, febuxostat. The efficacy of febuxostat was also examined in in vitro studies. RESULTS: We showed for the first time that the expression and the activity of XO were increased dramatically within the central nervous system of EAE mice as compared to naïve mice. Furthermore, prophylactic administration of febuxostat, a XO inhibitor, markedly reduced the clinical signs of EAE. Both in vivo and in vitro studies showed infiltrating macrophages and microglia as the major sources of excess XO production, and febuxostat significantly suppressed ROS generation from these cells. Inflammatory cellular infiltration and glial activation in the spinal cord of EAE mice were inhibited by the treatment with febuxostat. Importantly, therapeutic efficacy was observed not only in mice with relapsing-remitting EAE but also in mice with secondary progressive EAE by preventing axonal loss and demyelination. CONCLUSION: These results highlight the implication of XO in EAE pathogenesis and suggest XO as a target for MS treatment and febuxostat as a promising therapeutic option for MS neuropathology.